2002
DOI: 10.1046/j.1469-8137.2003.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nonnative earthworms on mycorrhizal colonization of sugar maple (Acer saccharum)

Abstract: Summary• Exotic earthworms can modify or eliminate surface organic (Oe/Oa) horizons in cold-temperate forest ecosystems and have profound effects on the forest soil environment, especially the rooting zone.• We examined the effects of earthworm colonization of northern hardwood forest soils on the abundance and morphology of mycorrhizal fungi associated with sugar maple ( Acer saccharum ). We compared mycorrhizal associations of areas of earthworm invasion with those of reference (no-worm) areas in Arnot Fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
3
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 49 publications
4
87
3
3
Order By: Relevance
“…Instead, we documented a positive association between Ovenbird density and core forest cover within 500 and 1,000 m radii. This finding was not unexpected, because impacts of Lumbricus in North America have been most commonly documented in maple-basswood forests, both within our study region (Gundale et al 2005;Hale et al 2005Hale et al , 2006Holdsworth et al 2007a, b) and in the northeastern U.S. (Lawrence et al 2003;Fox et al 2010). Studies finding Lumbricus impacts in other forest types are less common (but see Alban and Barry 1994;Nuzzo et al 2009).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Instead, we documented a positive association between Ovenbird density and core forest cover within 500 and 1,000 m radii. This finding was not unexpected, because impacts of Lumbricus in North America have been most commonly documented in maple-basswood forests, both within our study region (Gundale et al 2005;Hale et al 2005Hale et al , 2006Holdsworth et al 2007a, b) and in the northeastern U.S. (Lawrence et al 2003;Fox et al 2010). Studies finding Lumbricus impacts in other forest types are less common (but see Alban and Barry 1994;Nuzzo et al 2009).…”
Section: Discussionsupporting
confidence: 56%
“…We cannot completely overrule the possibility that density comparisons were affected by detectability differences between categories. However, since Lumbricus invasions reduce cover of plants, shrubs, and tree seedlings (Lawrence et al 2003;Hale et al 2006;Holdsworth et al 2007a;Nuzzo et al 2009), we would expect visual and auditory detection of songbirds to increase in ''thinned out'' invaded forests compared to Lumbricus-free forests. The magnitude of Ovenbird decline that we report would be conservative if this were the case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, other studies have reported that the incorporation of organic material into mineral soil by exotic earthworms increases soil microbial biomass (Burtelow et al 1998;Bohlen et al 1999;Li et al 2002;Groffman et al 2004). Modification of the soil matrix coupled with the feeding activity of earthworms can increase litter decomposition rates (Suárez et al 2006;Holdsworth et al 2008), change the availability and retention of soil carbon, nitrogen, and phosphorus (Bohlen et al 2004a,b;Suárez et al 2004;Hale et al 2005b;Szlavecz et al 2006), alter the size and structure of soil microbial (McLean and Parkinson 2000;Groffman et al 2004;McLean et al 2006;Dempsey et al 2011) and soil microfauna communities (McLean and Parkinson 1998;Migge-Kleian et al 2006), affect the abundance of arbuscular mycorrhizal fungi populations (Lawrence et al 2003), and change the distribution of plant fine roots . Depletion of the organic horizons and leaf litter layers by exotic earthworms can negatively impact the diversity and abundance of native plant species (Gundale 2002;Hale et al 2006;Nuzzo et al 2009;Hopfensperger et al 2011), though the magnitude of these effects may vary depending on site factors and the species of earthworm involved (Bohlen et al 2004c, Hale et al 2005bHale et al 2006;Holdsworth et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…通过影响凋落物和根的分解速率、C和N的矿化速 率、酶活性、微生物群落活动、土壤呼吸等,导致 生态过程和植物群落组成发生变化 (Alban & Berry, 1994;Burtelow et al, 1998;Groffman & Bohlen, 1999;Lachnicht et al, 2002;Lawrence et al, 2003;Li et al, 2002;Liu & Zou, 2002)。 Pontoscolex corethrurus为一种中等体型的热带 土居型蚯蚓,随着热带土地利用方式的变化,目前 已由其原居地南美洲入侵至全世界的许多热带湿 润地区 (González et al, 2006;Hendrix & Bohlen, 2002;Lavelle et al, 1987) (Berry & Jordan, 2001;Presley et al, 1996)。 土壤温度和湿度是影响蚯蚓生理特征和生态 行为的重要环境因素 (Presley et al, 1996),是调节蚯 蚓种群的关键因子 (Wever et al, 2001)。研究表明, 不同的土壤水分和温度条件下,蚯蚓的成熟时间、 产茧量、孵化能力和时间以及幼蚓的生长都有差异 (Ortiz-Ceballos et al, 2005;Uvarov & Scheu, 2004 (Haukka, 1987;Lavelle et al, 1987)。作为重要环境因素的土壤温度 和湿度是蚯蚓生存、生长、繁殖及维持和扩张种群 的主要非生物环境因素 (Wever et al, 2001)。作为在 热带地区的主要入侵种蚯蚓,P. corethrurus喜生存 在湿热的气候条件下,并且极易在人为干扰较强的 生境中定居或繁衍 (González et al, 2006;Lavelle et al, 1987;Liu & Zou, 2002) (Bhattacharjee & Chaudhuri, 2002),生长速率 在27.5%-55%土壤湿度范围内随湿度的增加而增 大,繁殖率在35%-55%土壤湿度范围内随湿度增 加而提高,而在土壤湿度低于35%时不能产茧(蚯 蚓不能达到成熟) (Lavelle et al, 1987) González et al, 1999;González et al, 2006;Zou & González, 1997 …”
unclassified